Analisis Efisiensi Penggunaan Masukan dan Ekonomi Skala Usaha pada Usahatani Tebu di Jawa Timur - Bambang Irawan; Budiman Hutabarat (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1991)
One of the governments approaches to improve the efficiency of sugarcane farming is by organizing farmer groups. This grouping of farmers aimed to increase the efficiency of farming in term of inputs use and farm size. The finding of this research show that in East Java, one of the important sugarcane area in Indonesia, the two category of sugarcane planting. For the ratoon planting the use of inputs was efficient but for the new planting the inputs used by farmers is quite small especially for labor input. Therefore the introduction of tractor for land preparation is suggested to eliminate the labor shortage. This research, has also shown that the economies of scale of sugar cane farming varied according to the category of planting. In order to find the optimal farming size, wet land sugarcane should be conducted in a larger farming size than that grown in dryland. The new planting of sugarcane is also suggested to be grown in larger farming size than ratoon planting.